A CROSS-SECTIONAL RESEARCH ON THE MENTAL TOUGHNESS OF RACKET GAMES AND COMBAT SPORTS PLAYERS - Singh, Maninder; Kaur, Manjit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose if this study was to determine the difference of Mental Toughness of Racket Games and Combat Sports Players. A total of three hundred male participants (N=300), aged 18 to 25, from universities in the northern region of India, were involved in the study. Additionally, these participants were divided into the following groups: Group: A: Racket Games (N1=150) and Group B: Combat Sports (N2=150). The current investigation employed the independent t-test. In hypothesis testing, 0.05 was used as the significance criterion. Self-Confidence: No significant variance difference (p = .871), so "Equal variances assumed" is used. The t-test is not significant (p = .625), indicating no meaningful difference in self-confidence. Motivation: No significant variance difference (p = .535), so "Equal variances assumed" is used. The t-test is not significant (p = .111), indicating no significant difference in motivation between the groups. Attention Control: No significant variance difference (p = .502), so "Equal variances assumed" is used. The t-test is not significant (p = .547), suggesting no meaningful difference in attention control. Goal Setting: No significant variance difference (p = .525), so "Equal variances assumed" is used. The t-test is not significant (p = .699), indicating no significant difference in goal-setting ability. Visual and Imagery Control: No significant variance difference (p = .428), so "Equal variances assumed" is used. The t-test is not significant (p = .273), suggesting no meaningful difference in visual and imagery control. Attitude Control: No significant variance difference (p = .811), so "Equal variances assumed" is used. The t-test is not significant (p = .119), indicating no meaningful difference in attitude control. Mental Toughness Total: No significant variance difference (p = .678), so "Equal variances assumed" is used. The t-test is not significant (p = .835), suggesting no significant difference in overall mental toughness.